2014
DOI: 10.1111/bjet.12212
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of dynamic learning analytics: Using university student data to increase retention

Abstract: With digitisation and the rise of e-learning have come a range of computational tools and approaches that have allowed educators to better support the learners' experience in schools, colleges and universities. The move away from traditional paper-based course materials, registration, admissions and support services to the mobile, always-on and always accessible data has driven demand for information and generated new forms of data observable through consumption behaviours. These changes have led to a plethora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 9 publications
1
60
0
Order By: Relevance
“…For the student audience in the study population, students enrolled part-time performed better in both face-to-face and online courses as compared to those enrolled full-time. The literature from other studies consistently found that full-time students were more likely to succeed (Adelman, 1999;Aragon & Johnson, 2008;Colorado & Eberle, 2010;Demetriou & Schmitz-Sciborski, 2011;de Freitas et al, 2015). There are many possible explanations for this finding, but not one identified in the existing literature.…”
Section: Predictors Of Academic Successmentioning
confidence: 93%
“…For the student audience in the study population, students enrolled part-time performed better in both face-to-face and online courses as compared to those enrolled full-time. The literature from other studies consistently found that full-time students were more likely to succeed (Adelman, 1999;Aragon & Johnson, 2008;Colorado & Eberle, 2010;Demetriou & Schmitz-Sciborski, 2011;de Freitas et al, 2015). There are many possible explanations for this finding, but not one identified in the existing literature.…”
Section: Predictors Of Academic Successmentioning
confidence: 93%
“…Other early concerns were highlighted as natural extensions of the logical outcomes of the research (de Freitas et al 2014); these approaches were not systematic inquiries into the potentially harmful effects of using student data. The ethics of opt-in/opt-out and consent (Prinsloo and Slade 2015;Hack 2015a), anonymity of data (de Freitas et al 2014), and expressly utilitarian ethics in learning analytics (Willis 2014) later emerged.…”
Section: Ethical Approaches To Student Data: a Reviewmentioning
confidence: 99%
“…The ethics of opt-in/opt-out and consent (Prinsloo and Slade 2015;Hack 2015a), anonymity of data (de Freitas et al 2014), and expressly utilitarian ethics in learning analytics (Willis 2014) later emerged. Kruse and Pongsajapan (2012) propose a move from learning analytics as applied to students by administrators and professors toward systems where students are equipped and enabled with their own data, though this approach also has potential ethical problems.…”
Section: Ethical Approaches To Student Data: a Reviewmentioning
confidence: 99%
“…Higher education institutions collect a vast amount of information from students regarding their use of e-learning resources in the form of activity logs and other digital footprints such as time and date, student demographics, course enrolments, survey questionnaires, library usage, and academic grades [8].…”
Section: Introductionmentioning
confidence: 99%